Relationship between obesity and iron deficiency anemia: is there a role of hepcidin?. Issue 8 (14th September 2018) - sal, Ertan; Yenicesu, Idil; Celik, Nurullah; Pasaoglu, Hatice; Celik, Bulent; Pasaoglu, Ozge Tugce; Kaya, Zühre; Kocak, Ulker; Camurdan, Orhun; Bideci, Aysun; Cinaz, Peyami
ABSTRACT: Objectives: Iron deficiency is common in obese children although the underlying mechanism is unclear. The aim of this study was to investigate the associations between iron parameters, leptin, hepcidin and adiponectin levels in obese children. Methods: A total of 237 children, ranging in age from 5 to 18 years, 180 with primary obesity and 57 healthy children and adolescents, were enrolled. Complete blood count, serum iron levels, iron-binding capacity, ferritin levels, leptin, hepcidin and adiponectin levels were studied. Results: White blood cell and platelet count, iron-binding capacity, high-sensitive C-reactive protein, leptin and hepcidin values in the obese group were higher than those of the control group ( p  < 0.001, p  = 0.002, p  < 0.001, p  < 0.001, p  < 0.001 and p  < 0.001, respectively). However, mean corpuscular volume, adiponectin and transferrin saturation values in the obese group were lower than in the control group ( p  = 0.026, p  = 0.003, and p  < 0.001, respectively). No significant differences were found in terms of hemoglobin, serum ferritin, iron and IL-6 levels. Conclusions: Our study suggests that hepcidin levels do not contribute to the development of iron deficiency anemia in pediatric obese individuals.